Talking to strangers : what we should know about the people we don't know - Gladwell, Malcolm (New York : Little, Brown and Company, 2019)
Examines why we fail to understand strangers, exploring cases from Sandra Bland to spies and financial fraud to demonstrate how our assumptions often mislead us.
(3z(BA Malcolm Gladwell book(3y (Blabel. Includes case studies and interviews. s
Includes bibliographical references and index.
Keywords: Interpersonal communication; Social psychology; Trust